Analysis of the Implementation of Collection of Income Tax Against Tax Arrears at the Jakarta Pratama Tax Service Office, Gambir Tiga - Harjo, Dwikora; Hernandeva, Azrie Ahmad; Safitri, Laila Gita; Kurnia, Rayhan Anandra; Stevvika, Salsabila (Sinergi International Journal of Accounting and Taxation, 2023)
Taxes are the biggest source of state revenue. The Jakarta Pratama Tax Office Gambir Tiga has the highest target slogan in second place at 98.53% in 2019 but drops significantly to the lowest in second from bottom at 81.12% in 2020. The purpose of this study is to find out more regarding the tax collection process and how it impacts on tax revenues. This study uses library research research methods by processing data through a qualitative descriptive analysis approach. Based on the data analysis conducted, it was concluded that the most effective and efficient billing process during the Covid-19 pandemic was the process of blocking taxpayer accounts. Factors that cause tax arrears against the biggest tax arrears at the Jakarta Primary Tax Service Gambir Tiga are taxpayer ignorance, lack of oversight, and negligence of taxpayers.